Eletroanálise de derivados acetaldeído com hidrazina e determinação em amostras de álcool combustível por voltametria de onda quadrada - Rodgher, Vanessa S. [UNESP]; Stradiotto, Nelson Ramos [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Barros, Aquiles A. (Sociedade Brasileira de Química, 2006)
A square wave voltammetric method is described for the determination of acetaldehyde using the derivatization reaction with hydrazine sulphate, based on the reduction of hydrazone generated as a product that exhibits a single well-defined peak at -1.19V in acetate buffer at pH 5. Calibration graphs were obtained from 1.0 x 10-6 mol L-1 to 10 x 10-6 mol L-1 of acetaldehyde, using a reaction time of 8 min and a hidrazine concentration of 0.02 mol L-1. The detection limit was 2.38 x 10-7 mol L-1. The method was applied satisfactorily to the determination of total aldehyde in fuel ethanol samples without any pre-treatment.
Electroanalysis of acetaldehyde derivatized with hydrazine and determination in fuel ethanol by square wave voltammetry
Keywords: acetaldehyde derivatization; reduction of acetaldehyde; fuel ethanol analysis